Penerapan dan Pandangan Keagamaan Terhadap Undang-Undang ITE di Indonesia - Indra Ramadona Harahap; Dewi Maharani (Journal of Social Responsibility Projects by Higher Education Forum, 2020)
Community service activities with the theme "Application and Views of Relevance to the ITE Law in Indonesia" aims to provide knowledge to students of SMA Negeri 4 The range of the importance of discussing the specific ITE Law for children and also looking at it from the religious side. The method used in this activity was a direct survey to the location of the school and also interviewed the Principal of SMA Negeri 4 Kisaran. ITE is information and electronic transactions in which a rule is made by the state with the help of information technology regarding the importance of trade and economic growth to realize the welfare of the community and the government needs to support the development of information technology through legal infrastructure and its regulation to help information technology be carried out secaa safely to avoid considering it with pay attention to the religious, social, cultural values ​​of Indonesian people